PENGARUH MODEL STAD BERBANTUAN VIDEO TERHADAP HASIL BELAJAR SISWA SMA PADA MATERI FUNGI - Andarwatiningrum, Nurul; Yeni, Laili Fitri; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research knew the influence of learning model type of Student Teams Achievement Divisions (STAD) helped by video on student learning outcomes in material fungi at 1st grade SMA Negeri  1 Sungai Raya. This research was a quasi experimental with on equivalent control group design. The study sample consisted of two class namely grade X IPA 4 as class experiment and grade X IPA 6 as grade control, the samples took by intact group. The instrument used was the multiple choice test with a total of 20 questions. The average learning outcomes in the experimental class was 13.75, while the control group was 12.72. The results of the U Mann-Whitney test analysis showed that , yaitu -1,49 > -1,96, it?s means there were differences between the learning outcomes of students taught using Student Teams Achievement Divisions (STAD) helped by video and the learning outcomes of students taught using a conventional learning model. The effect size obtained 0.32 in the medium category and gave the contribution 12.55 %. Keywords: Video, Learning Outcome, Fungi, STAD